Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1080/2162402x.2016.1234572
|View full text |Cite
|
Sign up to set email alerts
|

Responses to immune checkpoint inhibitors in nonagenarians

Abstract: The incidence of melanoma continues to rise with the most rapid increase seen in the elderly population. Historically, elderly patients with advanced melanoma have had dismal clinical outcomes, in part, due to distinct tumor biology, and often ineligibility for effective therapies during their development. In addition, due to relatively few geriatric patients being accrued to clinical trials of novel immunotherapeutics, there is a paucity of data regarding their safety and efficacy. Herein, we present the clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 39 publications
4
12
0
2
Order By: Relevance
“…In this population, we found that TVEC was well-tolerated and had a higher-than- 16,17 Our study finds that patients older than 75 responded similarly to TVEC therapy as those younger than 75. This recapitulates other studies showing that response to immunotherapies is not hampered by advanced age 18,19 and may even be enhanced 20 in the setting of decreased T regulatory cells.…”
Section: F I G U R E 1 Swimmer's Plot For Progression-free Survival (supporting
confidence: 90%
“…In this population, we found that TVEC was well-tolerated and had a higher-than- 16,17 Our study finds that patients older than 75 responded similarly to TVEC therapy as those younger than 75. This recapitulates other studies showing that response to immunotherapies is not hampered by advanced age 18,19 and may even be enhanced 20 in the setting of decreased T regulatory cells.…”
Section: F I G U R E 1 Swimmer's Plot For Progression-free Survival (supporting
confidence: 90%
“…A 28% response rate was also recently reported for urothelial bladder carcinoma patients older than 80 years who were treated with atezolizumab (vs 23% for all patients) . We have also reported cases of clinical benefit and response in patients older than 90 years, including a 90‐year‐old treated with a combination of ipilimumab and nivolumab who experienced a complete response and a 95‐year‐old with a partial response after pembrolizumab . We think that old age is not a contraindication to immune checkpoint inhibition and instead that functional status is a more relevant consideration.…”
Section: Extremes Of Agesupporting
confidence: 70%
“…46 We have also reported cases of clinical benefit and response in patients older than 90 years, including a 90-year-old treated with a combination of ipilimumab and nivolumab who experienced a complete response and a 95-year-old with a partial response after pembrolizumab. 53 We think that old age is not a contraindication to immune checkpoint inhibition and instead that functional status is a more relevant consideration. However, the overall toxicity profile, efficacy, and relative risks and benefits in comparison with other therapies have not been studied comprehensively for tumor types other than melanoma, and they will need further study.…”
Section: Extremes Of Agementioning
confidence: 99%
“…However, these small subgroups of patients were usually not analyzed separately. A series of 3 nonagenarian melanoma patients treated in two centers with immune checkpoint inhibitors was published in 2016 [11]. Two of these 3 patients had a primary mucosal melanoma (one nasal and the other anal).…”
Section: Discussionmentioning
confidence: 99%